The clash of civilizations: A historical perspective - Mohamad Zaidin, Mohamad; Kamaruzaman, Yusoff; Mohd Taufiq, Abd. Talib; Raja Hazirah, Raja Sulaiman; Nik Murshidah, Nik Din; Zaiton, Mustafa (2015)
Clash among humans, either individually or in groups is a normal phenomenon from forgotten times because interaction among humans is not always positive. Clashes can occur with the intention to control, protect interests to show-off to obtain natural resources and so forth. Thus, the question is why is this aspect of clashes exaggerated until, it has become a priority and imperative in interactions between humans and civilizations. Therefore, this study will survey the history behind the emergence of the term clash of civilizations from its beginning until recent times.